2010
DOI: 10.1016/j.ijgo.2010.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Care seeking for postpartum morbidities in Murshidabad, rural India

Abstract: Worldwide, an estimated 536 000 maternal deaths occur each year [1]. Of these, approximately 25% occur in India alone [2]. Postpartum maternal morbidity, defined by the WHO as morbidity occurring in the first 6 weeks after delivery, is a serious problem in resource-poor settings that contributes to maternal death [3]. Despite the high prevalence of postpartum morbidity and the danger of maternal mortality, women in low-resource settings such as rural India frequently fail to seek care from formal health provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 1 publication
1
12
2
Order By: Relevance
“…A study looking at factors influencing the use of maternal health care service in Madhya Pradesh found that Muslim women, and women belonging to non-ST, were more likely to receive ANC than other groups of women (53). Muslim women were found to be more likely to seek care for postpartum morbidities from formal providers as compared to Hindu women in a study conducted in rural West Bengal (82). An ethnographic study conducted in a rural Muslim village in Uttar Pradesh on perceptions and experiences in regards to institutional deliveries, showed how widespread mistrust toward the public health system, traditional practices in regards to the use of contraceptives and home deliveries, and poverty, interact in causing barriers for women to access skilled assistant at birth for Muslim women in this community (83).…”
Section: Resultsmentioning
confidence: 99%
“…A study looking at factors influencing the use of maternal health care service in Madhya Pradesh found that Muslim women, and women belonging to non-ST, were more likely to receive ANC than other groups of women (53). Muslim women were found to be more likely to seek care for postpartum morbidities from formal providers as compared to Hindu women in a study conducted in rural West Bengal (82). An ethnographic study conducted in a rural Muslim village in Uttar Pradesh on perceptions and experiences in regards to institutional deliveries, showed how widespread mistrust toward the public health system, traditional practices in regards to the use of contraceptives and home deliveries, and poverty, interact in causing barriers for women to access skilled assistant at birth for Muslim women in this community (83).…”
Section: Resultsmentioning
confidence: 99%
“…Delivery conducted either in a medical institution or home deliveries assisted by doctor/nurse/Lady Health Visitor (LHV)/Auxiliary Nurse Midwife (ANM)/other health professionals are termed as safe delivery [37]. The study considered postnatal care check-up within 42 days after child birth as a potential maternal healthcare service indicator [41], [42].…”
Section: Methodsmentioning
confidence: 99%
“…People consult IPs for a variety of common conditions, which include fevers, diarrhoea and respiratory problems (Rohde and Vishwanathan 1995; Kanjilal et al 2007; Gautham et al 2011; George and Iyer 2013) postpartum morbidity, anaemia and white discharge in women (Rao 2005; Tuddenham et al 2010) and newborn illnesses (Kaushal et al 2005). These providers tend to be viewed as a homogenous group, but studies in different settings suggest that they differ, in terms of education and training, the contents of their practice and their business model (Gautham et al 2011; George and Iyer 2013).…”
Section: Introductionmentioning
confidence: 99%